Urgensi Mata Kuliah Pendidikan Kewarganegaraan Di Kalangan Mahasiswa Generasi Z - Ajusman Ajusman; Muh. Wasith Achadi; Nurdhin Baroroh (Departement of Mathematics Education, 2024)
As technology advances, generation Z students can easily access foreign culture nowadays with the rapid flow of globalization making it easier for foreign culture to enter Indonesia. This is worrying about the development of the younger generation, especially generation Z, whose lives have been very spoiled by technology. A sense of nationalism is needed because of globalization and rapid technological progress. Civics and Pancasila education is one way to foster a sense of nationalism. The aim of this research is to determine the urgency of citizenship education courses among generation Z students in line with the rapid flow of globalization. The method used is library research (Library Research) by collecting and analyzing books and articles related to the theme. The results of this research show that citizenship education is very important for generation Z students, especially as their preparation to become the golden generation in 2045. In this increasingly complex era, understanding citizenship concepts such as rights and obligations, democracy, tolerance, pluralism, and participation in political and social life is very crucial. The various problems faced by the current generation are increasingly complex due to the massive presence of technology, for this reason the role of teachers and the urgency of citizenship education courses are very necessary which aims to shape students into humans or citizens who have a sense of nationality and love for their country.